2012
DOI: 10.1155/2012/569890
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Income Inequality: A Comparative Analysis

Abstract: This paper investigates whether the relationship between income inequality and growth changes over time. Two time periods, covering 1970–1985 and 1985–1999, are analyzed and compared. A statistically significant relationship between inequality and growth in either time period fails to emerge. However, there are indications that effect of inequality on growth may be different in the nineties when compared to the seventies. In the literature, a consistent negative effect of inequality on growth is documented alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 15 publications
1
11
0
2
Order By: Relevance
“…This finding is consistent with Woo's (2011) study using cross-country data set of 93 countries which concludes that there is a negative relationship between income inequality and long-term growth. Nissim (2007) and Binatli (2012) also provide the same conclusion that there is a negative relationship between the two variables. However, this finding is not in line with the study conducted by Li et al(2016) for the case of Chinese economy proving the empirical evidence that there exists a robust positive long-run relationship between income inequality and growth in post-reform China.…”
Section: The Results Of Panel Vector Error Correction Modelmentioning
confidence: 52%
See 1 more Smart Citation
“…This finding is consistent with Woo's (2011) study using cross-country data set of 93 countries which concludes that there is a negative relationship between income inequality and long-term growth. Nissim (2007) and Binatli (2012) also provide the same conclusion that there is a negative relationship between the two variables. However, this finding is not in line with the study conducted by Li et al(2016) for the case of Chinese economy proving the empirical evidence that there exists a robust positive long-run relationship between income inequality and growth in post-reform China.…”
Section: The Results Of Panel Vector Error Correction Modelmentioning
confidence: 52%
“…In contrast to these findings, Nissim (2007) proved that economic growth significantly reduces income inequality. Binatli (2012) concluded that economic growth was negatively and insignificantly associated with income inequality. Other empirical findings concluded that income inequality was associated with low growth rates (Pede et al 2009;Davis, 2007;Castello-Climent, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian lain mengenai pertumbuhan ekonomi dan ketimpangan memiliki hasil yang berbeda-beda di mana ketimpangan dapat berpengaruh secara positif dan negatif tergantung pada kondisinya (Binatli, 2012). Di Papua Barat, penelitian yang dihasilkan menyatakan bahwa pasca kebijakan otonomi daerah, ketimpangan sudah berada pada level medium yang berarti ketimpangan sudah berkurang pasca kebijakan tersebut dan terdapat perbaikan konstruksi dalam rangka meningkatkan pembangunan ekonomi (Nugraha et al, 2017).…”
Section: Kajian Pustaka Dan Perumusan Hipotesisunclassified
“…This scheme of identifi cation is considered more appropriate keeping in view the major hypothesis that, 'trade liberalization is detrimental to equality because it accelerated the deindustrialization in Pakistan'. Moreover, the globalization as tainted by several economic crises is expected to have implications for income inequality (Binatli (2012)). Herewith, the trade-off between GDP per capita and income inequality serves to test the Kuznets hypothesis (1995).…”
Section: Identifi Cation and Justifi Cation Of Variablesmentioning
confidence: 99%